2014
DOI: 10.1071/rj13122
|View full text |Cite
|
Sign up to set email alerts
|

Fire and carbon management in a diversified rangelands economy: research, policy and implementation challenges for northern Australia

Abstract: Burning of savanna is a globally important source of greenhouse gas (GHG) emissions. In Australia, burning of savanna contributes between 2% and 4% annually of the nation’s reportable emissions. Complete removal of this source of emissions is unrealistic because fire is a ubiquitous natural process and important land-management tool. In the rangelands of northern Australia, fire is used to manage habitat for conservation, control woodland thickening, manipulate pastures for grazing and is an essential componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…According to GFED4s, total annual tropical savanna fire emissions averaged 4.9 Pg CO 2 , 6 Tg CH 4 , and 0. of annual emissions. Experiments with early burning in Australia have shown a potential reduction of up to 50 % (Walsh et al, 2014), but it is not known to what extent it is possible to use this approach in other regions, what the side effects will be, and whether some of the mitigation will be offset by higher CH 4 emission factors because early season fires may occur when fuels have had less time to cure. In Australia the latter is probably not the case (Meyer et al, 2012), but whether this is found in other regions remains to be investigated.…”
Section: Greenhouse Gas Forcing Of Fires and Potential For Mitigationmentioning
confidence: 99%
“…According to GFED4s, total annual tropical savanna fire emissions averaged 4.9 Pg CO 2 , 6 Tg CH 4 , and 0. of annual emissions. Experiments with early burning in Australia have shown a potential reduction of up to 50 % (Walsh et al, 2014), but it is not known to what extent it is possible to use this approach in other regions, what the side effects will be, and whether some of the mitigation will be offset by higher CH 4 emission factors because early season fires may occur when fuels have had less time to cure. In Australia the latter is probably not the case (Meyer et al, 2012), but whether this is found in other regions remains to be investigated.…”
Section: Greenhouse Gas Forcing Of Fires and Potential For Mitigationmentioning
confidence: 99%
“…Attention has now turned to the productivity potential of the largely intact northern savanna landscapes, which will involve trade-offs between management of land and water resources for primary production and biodiversity conservation (Adams and Pressey, 2014;Grundy et al, 2016). Globally and in Australia, savanna fire ecology and fire-derived GHG emissions have been reasonably well researched (Beringer et al, 1995;Cook and Meyer, 2009;Livesley et al, 2011;Meyer et al, 2012;Walsh et al, 2014;van der Werf et al, 2010) and the impacts of fire on the functional ecology of the Australian savanna has been recently reviewed by Beringer et al (2015). In this study, we focussed on savanna deforestation and land preparation for agricultural use.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in the increase of fuels and a change in fire regimes, with larger, higher intensity uncontrollable wildfires able to occur, which had a negative impact on native vegetation (Jurskis and Underwood 2013). Today fire is seen as an important and integral part of the natural ecosystem of tropical and semi-arid savannas and is used as a land management tool where possible (Walsh et al 2014). However pastoralists involved in the cattle industry require improved pastures through introduced grasses and this has resulted in a number of exotic grasses invading native tropical and semiarid ecosystems (Driscoll et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in fire regimes can also directly impact community composition and structure with studies showing that fire can be used to manage habitat for conservation and natural resource management (Walsh et al 2014) and that a reduction in fire frequency can directly impact ecosystem composition and structure by allowing vegetation thickening (i.e. expansion of woody taxa) and encroachment to occur (Sheuyange et al 2005;Jurskis 2012;Jurskis and Underwood 2013;Murphy et al 2014;Moss et al 2016).…”
Section: Background and Gaps In Present State On Knowledgementioning
confidence: 99%
See 1 more Smart Citation